Hedychium in Traditional Healing Systems: An Ethnobotanical Review - Kripasree, R; Mani, Bince; Thomas, Tinu; Thomas, Sinjumol (Indian Forester, 2026)
Hedychium J. Koenig., is a genus in the ginger family, Zingiberaceae and is commonly seen in tropical and subtropical regions of Asia. They are mainly used in ornamental and medicinal purposes. Traditionally, the genus Hedychium has been used as medicine and in cultural ceremonies. Each part of the plant has its own unique healing properties. The Indian traditional system of medicine especially Ayurveda preferred various combination of this genus for the treatment of digestive, respiratory and inflammation related diseases. Rhizome of the plants of this genus is ginger like and have spicy flavour, so it is commonly used as food supplements. Rhizome is the major part that having great medicinal potential. Almost all the species of Hedychium possesses various kind of ethnomedicinal value.